The Resurrectionists - Collins, Michael, 1964- (Book collections on Project MUSE., 2021)
"Haunted by the deaths of his parents and uncle, Frank journeys north to dispute a cousin's claim to the family farm, where he meets a stranger who might resolve mysteries about Frank's past"--